THE DILEMMA OF ONLINE EDUCATION IN BUILDING STUDENT CHARACTER - Moh. Hafidurrahman; Samsul Arifin; Ach Sholehuddin (LP2M Institut Agama Islam Al-Khiarat Pamekasan, 2023)
This scholarly article critically evaluates the impact of technology, with a particular focus on online education, on students' morals and character. The research is designed to understand how online education, due to technological development, affects students' morals and character and to seek strategies to strengthen these aspects. The research methodology involved a comprehensive literature review, with data collected from various journals and the author's observation of the online education phenomenon. The results show that online education brings new challenges for students, including teachers' need for more direct guidance and the monotony of learning methods. This has an impact on the decline of students' morale and character. This article provides new insights into how technology affects students' morale and character, particularly online education. The study also highlights the importance of character and ethics education in the current education system and how online education can be customised to strengthen these aspects. In modern education, which is increasingly influenced by technology, this study contributes to understanding the challenges and opportunities posed by online education. As such, this article serves as a valuable resource for educators, researchers, and policymakers who seek to maximise the potential of online education while minimising its negative impact on students' morals and character